The Economics of Reindeer Herding: Saami Entrepreneurship between Cyclical Sustainability and the Powers of State and Oligopolies. - Reinert, Erik S. (2006)
This paper attempts to explain the drastic fall in income experienced by Saami reindeer herders in Northern Norway between 1976 and 2000, in spite of increasing government subsidies. Saami herders maintain a legal monopoly as suppliers of reindeer meat, a traditional luxury product in Norway. This paper shows that a review of the literature is supported by qualitative interviews. The paper argues that main explanatory variables are to be found in the interaction of a number of factors, mainly: cyclical climatic variation in Northern Norway; a system with fixed prices, independent of the variations in supply, that magnified the effects of the natural cycles; increasingly severe sanitary regulations forcing Saami herders to abandon slaughtering and preparation; and the oligopoly market powers of the non-Saami actors taking over slaughtering and processing. It is argued that the fall in herders’ income resulted from a failure of the Norwegian Department of Agriculture to understand key factors distinguishing sub-Arctic herding from sedentary agriculture. Sanitary requirements and the government’s quest for economies of scale in processing contributed to playing the volume of production into the hands of non-Saami oligopolies. In this way the Saami herders lost the meat production that traditionally was at the core of both their culture and their economic livelihood. Originality/value – The paper is relevant for the management of herding and other production systems in areas with cyclical production, and documents the damaging effects on the aboriginal culture resulting from Norway’s exclusive use of modern agricultural science in managing such systems.